Leptospermum flavescens Sm. protect pancreatic β cell function from streptozotocin involving apoptosis and autophagy signaling pathway in in vitro and in vivo case study - Hidayat, Ahmad Fadhlurrahman Ahmad; Chan, Chim Kei; Mohamad, Jamaludin; Kadir, Habsah Abdul (Elsevier, 2018)
Ethnopharmacological importance: Leptospermum flavescens has been used traditionally in Malaysia to treat various ailments such as constipation, hypertension, diabetes and cancer. Aim of study: To investigate the potential protective effects of L. flavescens in pancreatic β cells through inhibition of apoptosis and autophagy cell death mechanisms in in vitro and in vivo models. Materials and methods: L. flavescens leaves were extracted using solvent in increasing polarities: hexane, ethyl acetate, methanol and water. All extracts were tested for INS-1 β cells viability stimulated by streptozotocin (STZ). The extract which promotes the highest cell protective activity was further evaluated for insulin secretion, apoptosis and autophagy signaling pathways. Then, the acute toxicity of extract was carried out in SD rats according to OECD 423 guideline. The active extract was tested in diabetic rats where the pancreatic β islets were evaluated for insulin, apoptosis and autophagy protein. Results: The methanolic extract of L. flavescens (MELF) was found to increase INS-1 β cells viability and insulin secretion against STZ. In addition, MELF has been shown to inhibit INS-1 β cells apoptosis and autophagy activity. Notably, there was no toxicity observed in SD rats when administered with MELF. Furthermore, MELF exhibited anti-hyperglycemic activity in diabetic rats where apoptosis and autophagy protein expression was found to be suppressed in pancreatic β islets. Conclusion: MELF was found to protect pancreatic β cells function from STZ-induced apoptosis and autophagy in in vitro and in vivo.